Medical cannabis or cannabinoids for chronic non-cancer and cancer related pain: a systematic review and meta-analysis of randomised clinical trials. (8th September 2021) - Wang, Li; Hong, Patrick J; May, Curtis; Rehman, Yasir; Oparin, Yvgeniy; Hong, Chris J; Hong, Brian Y; AminiLari, Mahmood; Gallo, Lucas; Kaushal, Alka; Craigie, Samantha; Couban, Rachel J; et al.
Abstract: Objective: To determine the benefits and harms of medical cannabis and cannabinoids for chronic pain. Design: Systematic review and meta-analysis. Data sources: MEDLINE, EMBASE, AMED, PsycInfo, CENTRAL, CINAHL, PubMed, Web of Science, Cannabis-Med, Epistemonikos, and trial registries up to January 2021. Study selection: Randomised clinical trials of medical cannabis or cannabinoids versus any non-cannabis control for chronic pain at ≥1 month follow-up. Data extraction and synthesis: Paired reviewers independently assessed risk of bias and extracted data. We performed random-effects models meta-analyses and used GRADE to assess the certainty of evidence. Results: A total of 32 trials with 5174 adult patients were included, 29 of which compared medical cannabis or cannabinoids with placebo. Medical cannabis was administered orally (n=30) or topically (n=2). Clinical populations included chronic non-cancer pain (n=28) and cancer related pain (n=4). Length of follow-up ranged from 1 to 5.5 months. Compared with placebo, non-inhaled medical cannabis probably results in a small increase in the proportion of patients experiencing at least the minimally important difference (MID) of 1 cm (on a 10 cm visual analogue scale (VAS)) in pain relief (modelled risk difference (RD) of 10% (95% confidence interval 5% to 15%), based on a weighted mean difference (WMD) of −0.50 cm (95% CI −0.75 to −0.25 cm, moderate certainty)). Medical cannabis taken orally results in a very small improvement in physical functioning (4% modelled RD (0.1% to 8%) for achieving at least the MID of 10 points on the 100-point SF-36 physical functioning scale, WMD of 1.67 points (0.03 to 3.31, high certainty)), and a small improvement in sleep quality (6% modelled RD (2% to 9%) for achieving at least the MID of 1 cm on a 10 cm VAS, WMD of −0.35 cm (−0.55 to −0.14 cm, high certainty)). Medical cannabis taken orally does not improve emotional, role, or social functioning (high certainty). Moderate certainty evidence shows that medical cannabis taken orally probably results in a small increased risk of transient cognitive impairment (RD 2% (0.1% to 6%)), vomiting (RD 3% (0.4% to 6%)), drowsiness (RD 5% (2% to 8%)), impaired attention (RD 3% (1% to 8%)), and nausea (RD 5% (2% to 8%)), but not diarrhoea; while high certainty evidence shows greater increased risk of dizziness (RD 9% (5% to 14%)) for trials with <3 months follow-up versus RD 28% (18% to 43%) for trials with ≥3 months follow-up; interaction test P=0.003; moderate credibility of subgroup effect). Conclusions: Moderate to high certainty evidence shows that non-inhaled medical cannabis or cannabinoids results in a small to very small improvement in pain relief, physical functioning, and sleep quality among patients with chronic pain, along with several transient adverse side effects, compared with placebo. The accompanying BMJ Rapid Recommendation provides contextualised guidance based on this body of evidence. Systematic review registration: https://osf.io/3pwn2